BALANCING ENVIRONMENTAL RULES WITH THE FUTURE OF OIL AND GAS - Singh, Meghna; Kumar, Mahendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The oil and gas industry plays a pivotal role in the global economy but poses significant environmental risks through pollution and climate impacts during exploration and production. Nations have enhanced their energy sector operations to balance economic growth with environmental conservation. This study examines global regulatory frameworks governing oil and gas exploration and production (E&P), focusing on environmental concerns. It analyzes policies and decision-making processes of key international organizations like the UNFCCC, OPEC, and IEA, emphasizing sustainability in resource extraction. Challenges in implementing international agreements include weak enforcement, varying national regulations, data transparency issues, and inadequate monitoring systems. The study concludes that achieving sustainability requires collaborative efforts, standardized practices, enhanced monitoring, and increased financial support. A sustainable future in energy E&P depends on global cooperation and shared responsibility.